Intravenous infusion of engineered megakaryocytes to produce oncolytic platelets in vivo for enhanced cancer immunotherapy - Yinxian Yang; Shenqiang Wang; Xueying Shi; Xudong Chen; Ruyi Zhou; Tao Sheng; Xiaofeng Chen; Jinpeng Han; Yan Xu; Qing Wu; Yuqi Zhang; Hongjun Li; et al. (Proceedings of the National Academy of Sciences, 2026)
Tumor-targeted delivery of oncolytic viruses (OVs) via systemic administration could not only expand virotherapy beyond primary tumors to widespread metastases, but also improve clinical adherence and convenience. We here engineer megakaryocytes encapsulating oncolytic adenovirus type 5 (M-Ad5) to produce oncolytic platelets in vivo by leveraging the thrombopoiesis process. Upon intravenous administration, M-Ad5 travels through the lungs, where it can release OVs-harbored therapeutic platelets into circulation under pulmonary turbulence microenvironments. Under the shelter of platelets, OVs resist inactivation by neutralizing antibodies and actively target widespread noninjectable cancer lesions. Intravenous infusion of M-Ad5 to mice with A549 lung cancer could significantly inhibit tumor growth and prolong survival. In multiple mouse tumor models, M-Ad5 induced a robust antitumor immune response by reprogramming the immunosuppressive tumor microenvironment, and potentiated the response to immune checkpoint inhibitors by recruiting more immune cells. We demonstrated that M-Ad5 in combination with PDL1 inhibitors activated tumor antigen-specific CD8 + T cells and memory T cells, thereby suppressing the growth of CT26 colorectal cancer metastasis, and preventing postsurgical B16F10 cancer recurrence and metastatic spread, as well as providing long-term immune protection against the rechallenged tumors.